Experiment with Freedom Every Day: Regarding the Visual Dimension of Homiletics (Homiletic, 2011)
The primary ways in which Homiletics has traditionally developed have been through oratory and literary sciences. Today, however, communication is being influenced more and more by computer-mediated communications. Literary science has begun to move further into various means of electronic communication using signs and symbols, and it is for this reason that homiletics should also be discussed in the context of communication sciences. The phenomenon of virtual reality provides a foundation for this discussion, and it can be included in the discourse in many fruitful ways. Virtual realities open up the interpretation of actual realities to a variety of new possibilities, and cultivate a keener perception of the imperfect parts of our lives. In this way they show that reality is comprised of much more than only that which appears to be real. Homiletics can benefit from this in several different regards: 1) by generating open-ended worldviews, 2) by opening homiletics more to the future and 3) by activating the body for experimenting with freedom every day.